Design of SCoPE health education module on internet addiction prevention among undergraduate students: study protocol for a cluster randomized controlled trial - Mashudi, Dina Nurfarahin; Ahmad, Norliza; Mohd Zulkefli, Nor Afiah; Tan, Kit-Aun (Universiti Putra Malaysia Press, 2024)
Introduction: Internet addiction is prevalent among undergraduate students. A meta-analysis including 80 primary studies reports from 31 nations found a prevalence rate of 6% globally. However, a specific study of 480 undergraduates found a much higher prevalence of 78.7%, highlighting the urgent need for prevention studies in this area. Therefore, this study protocol outlines the methodology and design of the trial, which aims to develop, implement, and evaluate the effects of the SCoPE module based on the Health Belief Model in Internet addiction prevention among undergraduate students. Methods: The study is a single-blind cluster randomised controlled trial at a public university, focusing on undergraduate students. Faculties are the unit of randomisation. Twelve faculties will be randomised into intervention group and wait-list control group. The primary outcome of this study is Internet addiction test scores, while the secondary outcomes are knowledge of Internet addiction and six Health Belief Model’s constructs. The SCoPE health education module includes six animated videos and synchronous WhatsApp group discussions. Participants will adhere to a structured six-day schedule, devoting 10 minutes to each video session and 20 minutes to discussion sessions daily. Measurements occur at baseline (T0), immediately post-intervention (T1), and 3-month post-intervention (T2). Discussion: The present study would demonstrate the successful application of the Health Belief Model in designing the SCoPE health education module which is aimed to prevent Internet addiction among undergraduate students at public universities, serving as a blueprint for future modules to mitigate Internet addiction among undergraduate students in Malaysia. Trial Registration: Clinical Trial Registry-Thailand (CTRT) TCTR20230408003.